2006
DOI: 10.1111/j.1468-1293.2006.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and neurocognitive performance in individuals with HIV/AIDS: 2‐year follow‐up

Abstract: ObjectivesThe aims of this study were to follow a cohort of HIV-infected individuals for 2 years to assess changes in depression and neuropsychological performance over time, to explore the relationship between depression, HIV illness and neuropsychological performance, and to examine the natural history of the effect of highly active antiretroviral therapy (HAART) on depression and neurocognitive performance.Methods HIV-seropositive out-patients were assessed at baseline and at 2-year follow-up. At each asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 28 publications
3
54
0
2
Order By: Relevance
“…42 Other authors reported similar findings in different populations of HIV-infected patients treated with HAART (Table 1). 22,33,35 These observations were supported by the analysis of two cohorts performed before and after the advent of HAART showing no difference in the overall occurrence of HIV dementia and NP abnormalities. 13 Similarly, Cysique et al reported that the prevalence of NP impairment was not different across pre-HAART and HAART eras.…”
Section: Variable Benefits From Haartsupporting
confidence: 64%
See 2 more Smart Citations
“…42 Other authors reported similar findings in different populations of HIV-infected patients treated with HAART (Table 1). 22,33,35 These observations were supported by the analysis of two cohorts performed before and after the advent of HAART showing no difference in the overall occurrence of HIV dementia and NP abnormalities. 13 Similarly, Cysique et al reported that the prevalence of NP impairment was not different across pre-HAART and HAART eras.…”
Section: Variable Benefits From Haartsupporting
confidence: 64%
“…Interestingly, several interactions with depression scores were noted in this study since patients without depression improved significantly at cognitive testing while those with depression did not. 22 Stable or improving cognition over a 2-year period was also reported in advanced HIVinfected patients. 35 Within the randomized, double-blinded, controlled ACTG 5095 trial, a battery of three NP tests was administered to 303 ARV-naive patients randomly assigned to zidovudine-lamivudine-abacavir or zidovudine-lamivudineefavirenz or zidovudine-lamivudine-abacavir-efavirenz.…”
Section: Haart Improves Neurocognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 In addition, patients who demonstrate depression and cognitive impairment together may not respond well to treatment. 58 Instruments to assess depression that allow one to separate out items describing somatic symptoms from those concerning depressed mood should be used, as somatic symptoms associated with depression may also be caused by HIV infection. 20 Some neuropsychological test may help in differentiating patients with HIV cognitive impairment with and 1 12 20 0 without depression.…”
Section: Depressionmentioning
confidence: 99%
“…Further, such testing provides the advantages of standardized administration and scoring with minimal training of evaluators. Existing computerized batteries, such as the CANTAB and Cog-State, are useful for assessment of mild cognitive deficits and for tracking changes in cognition over time [20,21], but neither has been well validated in HIV-infected patients with mild cognitive deficits. In addition, these tests are expensive to purchase and maintain.…”
mentioning
confidence: 99%